Reusable, homogeneous water soluble photoredox catalyzed oxidative dehydrogenation of N-heterocycles in a biphasic system: application to the synthesis of biologically active natural products. Issue 8 (7th April 2020) - Srinath, S.; Abinaya, R.; Prasanth, Arun; Mariappan, M.; Sridhar, R.; Baskar, B.
Abstract : Herein, a simple and efficient method for the oxidative dehydrogenation (ODH) of tetrahydro-β-carbolines, indolines and (iso)quinolines is described using a reusable, homogeneous cobalt-phthalocyanine photoredox catalyst in a biphasic medium. Abstract : Herein, a simple and efficient method for the oxidative dehydrogenation (ODH) of tetrahydro-β-carbolines, indolines and tetrahydro-(iso)quinolines is described using a reusable, homogeneous cobalt-phthalocyanine photoredox catalyst in a biphasic medium. A biphasic system offers an advantage of easy separation of the product and an efficient reusability of the homogeneous photoredox catalyst. Also, the current system significantly helps to overcome the solubility issue of the substrate and catalyst at room temperature. Its potential applications to organic transformations are demonstrated by the synthesis of various biologically active N-heterocycles such as indoles, (iso)quinolines and β-carbolines and natural products such as eudistomin U, norharmane, and harmane and precursors to perlolyrine and flazin. Without isolation and purification, the catalyst solution can be reused up to 5 times with almost comparable reactivity. Furthermore, the efficiency of the reaction was demonstrated on a gram scale. To the best of our knowledge, this is the first report on ODH reactions using a non noble, reusable and homogeneous cobalt photoredox catalyst under environmentally friendly conditions.